Comparison of two hydrological model simulations using NAM and XINANJIANG for Nong Son catchment - Nghi, Vu Van; Lam, Dang Thanh; Dung, Do Duc (Vietnam Journal of Mechanics, 2008)
The study presents the hydrological simulations for the Nong Son catchment, a drainage area of the Vu Gia-Thu Bon basin in the Central Vietnam, by using the NAM and XINANJIANG models. Simulation results for both models show good agreement between calculated and observed discharges at the stream gauge. The overall water balance error is less than ±10%, Nash-Sut cliffe efficiency \(R^2\) above 0.85, and Pearson correlation coefficient \(r\) above 0.92 in both model calibration and verification period. Although NAM’s performance shows a slightly better correspondence between the discharges at the stream gauge, the XINANJIANG model shows a relatively better reproduction of the runoff components (i.e. overland flow, interflow and baseflow)